'Radiations in Industry' - TUC booklet, 1960 (1960)
1960 1945-1960 "'Radiations in Industry' - TUC booklet, 1960" [T0356.jpg], 1960, Trades Union Congress This illustrated booklet was produced by the TUC to explain radiation and radioactive substances, how and where they are used and the health and safety precautions required. It is mainly concerned with the protection of workers exposed to ionising radiation but also looks at the wider risks of nuclear reactors, etc.